HORROR AS A SPECTACLE: AN ANALYSIS OF THE CONFLICT BETWEEN HAMAS AND ISRAEL IN 2023 - Aparecido Gonçalves, Israel; Aldenora dos Santos Lima, Maria (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this article is to analyze the conflict (which has not yet ceased) between the State of Israel and the Gaza Strip, which began on October 7, 2023. Scenes of murders, war, and human drama were posted on social networks and in the mainstream media (Globo, Globo News, CNN) in a selected manner. 4,687 online articles were also recorded from the newspapers Estadão and FSP, in addition to the G1 portal. In addition, there is an analysis of 3 channels on Instagram, specialized in military matters, which publicize scenes of the massacres. We showed that the horror scenes shown by the mainstream media and social networks, especially the latter, contained few restrictions on the exposure of information, with the aim of getting likes and followers, thus the horror became a spectacle.